2005
DOI: 10.1159/000084850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Space Flight Conditions on the Function of the Immune System and Catecholamine Production Simulated in a Rodent Model of Hindlimb Unloading

Abstract: The rodent model of hindlimb unloading has been successfully used to simulate some of the effects of space flight conditions. Previous studies have indicated that mice exposed to hindlimb-unloading conditions have decreased resistance to infections compared to restrained and normally housed control mice. Objective: The purpose of this study was to clarify the mechanisms involved in resistance to infection in this model by examining the effects of hindlimb unloading on the function of the immune system and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 64 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…Both HU and CRS are physical stress models containing a significant psychological component that activates neural transmitters and stress hormones (Aviles et al, 2005;Dhabhar et al, 2000). Until now, the role of OPN in the stress response of immune organs has not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both HU and CRS are physical stress models containing a significant psychological component that activates neural transmitters and stress hormones (Aviles et al, 2005;Dhabhar et al, 2000). Until now, the role of OPN in the stress response of immune organs has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here imply an involvement of macrophages, which share the same lineage with osteoclast, in the remodeling of the lymphoid organs in response to HU stress. OPN has in fact been implicated in both macrophage and osteoclast function (Rittling et al, 1998;Aviles et al, 2005). OPN is produced by both cell types and facilitates their function(s), in part via interactions with CD44.…”
Section: Opn Is Implicated In Immune and Inflammatory Responses For mentioning
confidence: 99%
“…Mice were caged individually and suspended for 3 days by the tail by using a strip of adhesive surgical tape attached to a chain hanging from a pulley. Mice were suspended at a 25°angle to the f loor with only the forelimbs touching the f loor (24,38). Food and water were supplied ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Although a great deal of evidence suggests that stress-induced neurohormones play a critical role in the outcome of infections (1,3,4,5,7,21,31), the mechanisms by which these hormones act in the host remain unclear. Studies with human and animal models have indicated that increased levels of stress hormones, including norepinephrine (NE), as well as other catecholamines, alter the immune response and physiology of the host (2). High circulatory levels of these hormones are detected in individuals exposed to a variety of physically and/or mentally stressful situations, including trauma, space flight, and sepsis (13,29,31,32).…”
mentioning
confidence: 99%